Thermogravimetric analysis of combustion characteristics and kinetics of hydrothermally treated and washed empty fruit bunch. Issue 8 (14th September 2021) - Ruksathamcharoen, Sirawasith; Chuenyam, Teerapong; Ajiwibowo, Muhammad W.; Yoshikawa, Kunio
Abstract: This study aims to study the fuel properties, combustion behaviors and kinetics of hydrothermally treated and washed empty fruit bunch (HTW-EFB). For the lab-scale samples, EFB was hydrothermally treated (HT) at 180, 200 or 220 °C for 30 min and washed using water at 60 °C for 15 min to remove alkaline metals. For the commercial-scale sample, EFB was HT at 2 MPa for 30 min and washed with room temperature water using a centrifugal machine. Results indicate that a combination of hydrothermal and washing treatments (HTW) improved fuel properties of EFB significantly, with an increase in calorific value to 2.33 × 10 4 kJ kg −1 and a reduction in the alkaline contents. Significant shifts in combustion behavior were observed when EFB underwent HTW. The ignition temperature of the hydrochars was 290–296 °C with the burnout temperature at 438–485 °C. From the kinetic study, a first-order reaction and one-dimensional diffusion is the main mechanism in the combustion of volatiles, while one-dimensional diffusion is the main mechanism for the combustion of the fixed carbon of the hydrochars. The activation energy of HTW-EFBs was between 99.96 and 138.26 kJ mol −1 in the devolatilization stage and 10.97–27.56 kJ mol −1 in the char oxidation stage.